An intrusion detection system (IDS) for internet network - Safiee, Mohd. Fauzan (2007)
An Intrusion Detection System (IDS) is detects and blocks unwanted attacks to the civilian or the military systems. These attacks can be an internal attack or external attack. The traffic or the normal networks is heterogeneous where else the military network has more homogeneous traffic. Even though the internet security includes firewall and other system security it usually failed to filter out the unwanted attack to the system and allows system breakdown and system failures. The major problems in developing the IDS method is the evolving growth of the internet topology and the growth of the internets users which makes the modeling of the network with attack free data is difficult. Real world test has shown overwhelming numbers of false alarms of attack and little success in filtering them out. This project is to analysis the network with data free attacks in a simulator that involved selfsimilar traffic that ideally represents the internet traffic modeling as well as the Poisson traffic modeling for the non peak hours periods. With templates of data free attacks a system will reduce the complexity in detecting the attacks during peak hours and non peak hours. The network system was simulated in NS-2 simulator.